Need Analysis dalam Pengembangan Kurikulum - Siti Khasinah; Elviana Elviana (Jurnal MUDARRISUNA: Media Kajian Pendidikan Agama Islam, 2022)
This article describes the importance of need analysis or need assessment in the development of a curriculum in educational institutions considering that the success of an educational program is highly dependent on how effectively the curriculum can be implemented. This article is expected to help provide understanding to teachers, lecturers, or certain parties who contribute to curriculum development activities related to the implementation of needs analysis. For this reason, two main issues are the focus of this paper, namely curriculum development and needs analysis. Matters relating to needs analysis begin with definitions, objectives, focus, and implementation procedures supported by several references such as books and research results.